(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
This article examines the impact of 3D printing on the textile and fashion industry, highlighting its potential to revolutionize production processes, reduce environmental impacts, and enable mass customization. Through a literature review, the study demonstrates how this technology facilitates the creation of clothing, accessories, and smart textiles with complex structures while minimizing waste through on-demand production. The findings reveal advancements in flexible materials, such as thermoplastic polyurethane (TPU), thermoplastic elastomer (TPE) and sustainable alternatives, such as polylactic acid (PLA, bio inks), illustrated by case studies such as Iris Van Herpen and Danit Peleg. The Fused Deposition Modeling (FDM) technique stands out for its versatility, enabling direct printing on fabrics as well as the production of electronic wearables. However, challenges remain, including limitations in breathable materials, scaling costs, and regulatory issues related to intellectual property. The study concludes that 3D printing, aligned with ethical and environmental values, has the potential to redefine the textile industry by combining creativity, efficiency, and socio-environmental responsibility provided there is multidisciplinary collaboration and investment in research on biocomposites and decentralized logistics.